Entrepreneurial Skills and Characteristics Analysis on the Graduates of the Department of Administrative Sciences, FISIP Universitas Indonesia - Fitriati, Rachma; Hermiati, Tutie (UI Scholars Hub, 2011)
This research aims to study the skills and characteristics (attributes) of entrepreneurship required of the graduates of the Department of Administration Science, Faculty of Social and Political Sciences, Universitas Indonesia. This research used a quantitative approach; the data collection techniques are questionnaires and in-depth interviews. The results show that each study program in the Department of Administration Science needs to acquire entrepreneurial skills and characteristics. This research suggests that the lecture material provision be equipped with entrepreneurial skills and characteristics in order that the graduates of Administration Science Department have added value in the labor market. Entrepreneurship becomes an interesting study, especially since it is closely related to the concept of building entrepreneurial process, required of the graduates of the Department.